Immorality judgments and framing effects in voluntary payment settings - Elisa Hofmann; Deliah Bolesta; Aya Adra (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
The Theory of Dyadic Morality (TDM; Schein and Gray (2018)) posits that immorality judgments emerge from norm violations, harm perceptions, and negative affect. We test this core prediction in an applied setting: voluntary payment settings, such as the Pay-What-You-Want mechanism. In our study, we assess own payment intentions and how voluntary payments of an ostensible individual for an online-news website are judged by participants regarding their perceptions of immorality, harm, anger, and social norms. As political orientation is a key variable in theorizing and exploring immorality judgments in psychological research, we take its potential impact into account in our study. Because voluntary payments have been shown to be sensitive to framing, we vary the pricing mechanism's name in a between-subjects one-factorial design with four factor levels (Pay-What-You-Want, You-Can, It-Is-Worth-To-You, You-Believe-Is-Fair). The results of our online experiment with 602 Americans indicate that voluntary payment settings are indeed perceived as moral domains. We find that perceptions of norm violation, harm, and negative affect predict immorality judgments, lending empirical support to the Theory of Dyadic Morality. We also show that these components, the immorality judgments, and the own payment intentions are sensitive to framing effects. Finally, we find substantial differences between liberals and conservatives, suggesting an ideological influence on immorality judgments.
Keywords: C99; D01; D91; L11; 330; Theory of Dyadic Morality; immorality judgments; experiment; voluntary payments; Pay-What-You-Want; framing; social norms